Persistent prion infection disturbs the function of Oct-1, resulting in the down-regulation of murine interferon regulatory factor-3 - Homma, Takujiro (Nature Publishing Group, 2014)
As a prompt response against invasion of various viruses, interferon regulatory factor-3 (IRF-3) is initially phosphorylated to become activated and upregulates mainly Type I Interferons (IFN-I) in most cell types. We previously reported that IRF-3-dependent host innate immune responses partially interfere in infection of prions. Here, we found that stable infection of prion suppressed IRF-3 gene-expression. The decreased promoter activity of IRF-3 was significantly restored along with treatment of anti-prion drugs in the prion-infected cells, suggesting that infection of prion directly influence the regulation of IRF-3 transcription. We further investigated promoter activity of 5′- flanking region of murine IRF-3 using a luciferase reporter system and found that the nucleotides -119 to -1 were indispensable for the promoter activity. Within this region, mutations in the Oct-1 binding site significantly reduced the promoter activity and chromatin immunoprecipitation (ChIP) assay revealed that Oct-1 indeed binds to the region. In addition, overexpression of Oct-1 increased the promoter activity of IRF-3. Intriguingly, Oct-1 protein was significantly reduced in prion-infected cells and mice brains compared with uninfected groups. Taken together, we concluded that prion infection could interfere in the function of Oct-1, resulting in the down-regulation of IRF-3.